Varietal effects on price-spread and milling recovery of rice in Nepal - Pant, Krishna P; Aryal, Maniratna (Journal of Agriculture and Environment, 2014)
General complaint of Nepalese farmers is that middlemen grasp much of the benefits from agricultural products paying low to farmers and charging high to the consumers thereby discouraging farmers to produce. Scientific studies are scanty to support or refute the complaint. The main objective of this paper is to test this hypothesis in light of rice recovery in milling. Primary data were collected from surveys of randomly selected 50 households and 41 mills from purposively selected 19 districts in Nepal. The study found that the rice recovery rate is 66.2% for head rice 73.2% for brown rice. After adjusting for the milling percent the retail price comes to be 14% to 18% higher than the farm gate price. The results show that the marketing margin is not so wide in case of less perishable crops like rice. Improving milling technology, however, can increase milling percent reducing the price spread.